PWE-142 State of The Endoscopy Services in Bangladesh- First Nationwide Survey. (17th August 2016) - Rahman, MM; Rahman, MM; Dave, UR; Hossain, MJ; Kibria, MG; Nuruzzaman, M; Ahmed, F; Rowshon, A; Hasan, M; ,
Abstract : Introduction: We conducted survey on endoscopy centres in Bangladesh with the aim to assess the current status and to identify areas to improve standards in services. Methods: All endoscopy centres in the country were identified from endoscope vendors, Bangladesh Gastroenterology society (BGS) member list and personal communication. A Structured questionnaire containing mainly structural, process and outcome measures along with a letter from BGS were sent to a senior endoscopist of every centre who completed the questionnaire. Data was analysed anonymously. Results: Questionnaire sent to all 197 endoscopy centres and 195 centres responded (response rate 99%). Of those 12% were public and 88% were privately run endoscopy centres. More than half (52%) were diagnostic centres (39%) or clinics (13%) and rest were in hospital setting (48%). Gastroscopy, colonoscopy, flexible sigmoidoscopy, ERCP and EUS were done at 100%, 65%, 37%, 13% and 2% centres. Total 356251 gastroscopy, 51252 colonoscopy, 10824 flexible sigmoidoscopy, 4123 ERCP and 291 EUS were done in the year (October 2014 to September 2015) with a rate of 227, 33, 6.9, 2.63 and 0.19 per 100, 000 people respectively. Majority performed only diagnostic gastroscopy (53%) in a single room unit (76%) with no dedicated recovery areas and majority never used sedation (59%). Paediatric Gastroenterologists available in 2% of 61% centres performing endoscopy on children. Computerised reports with photo provided by 97% centres and majority kept records (92%). 38% of centres were run by a single endoscopist while 9% had five or more endoscopists. Only 5% of centres had trainee endoscopists. Majority did not have registered endoscopy nurse (59%) or clerical staff (52%). Most centres had single scope (Gastroscope 76%, colonoscope 78%). Automated sterilisation system available in 3 centres and 31% reported sterilisation before procedures. Centres using sedation (41%) only 43% of them kept antidotes for sedative agents. Information leaflet for gastroscopy and colonoscopy provided by 34% and 65% and signed consent form by 35% and 80% centres respectively. Few kept records of procedure related complications (26%) and only 18% carried out regular audit. Conclusion: This first ever nationwide survey on endoscopy centres provided baseline data. The study is exploring the current status and standards in endoscopy in Bangladesh which will help to identify the limitations and scope for improvements and act as a first building block. Disclosure of Interest: None Declared